Novel results on SCTP multihoming performance in native IPv6 UMTS-WLAN environments. (6th July 2010) - Bokor, Laszlo; Huszak, Arpad; Jeney, Gabor
Multihoming is one of the most attractive features of stream control transmission protocol (SCTP) aiming to make this prosperous transport scheme competitive in mobile environments when the mobile hosts are equipped with multiple interfaces. The complementary characteristic of the 3G universal mobile telecommunications system (UMTS) and wireless local area network (WLAN) architectures motivates operators to integrate these two successful technologies. Recently spreading wireless devices are increasingly provided with multiple networking interfaces such enabling end-users to access internet services using e.g., the WLAN's higher bandwidth wherever available, and connecting to the UMTS network in other cases. This paper investigates the performance of multihomed SCTP hosts through extensive experimental studies in such an integrated heterogeneous environment. In order to do this, we designed and implemented a real native IPv6 UMTS-WLAN testbed equipped with novel IPv6-based mobile technologies, such providing ideal conditions for SCTP multihoming performance analysis. In this testbed architecture we analysed numerous settings to measure the handover behaviour of the protocol in terms of handover effectiveness, link changeover characteristics, throughput and transmission delay. As our results show, accurate SCTP parameter setup can significantly decrease the handover delay and eliminate the data transmission interrupts.